Automated assessment of a kinetic database for fcc Co–Cr–Fe–Mn–Ni high entropy alloys. (20th May 2021) - Abrahams, Katrin; Zomorodpoosh, Setareh; Khorasgani, Ahmadreza Riyahi; Roslyakova, Irina; Steinbach, Ingo; Kundin, Julia
Abstract: The development of accurate kinetic databases by parametrizing the composition and temperature dependence of elemental atomic mobilities, is essential for correct multicomponent calculations and simulations. In this work the automated assessment procedure for the establishment of CALPHAD-type kinetic databases is proposed, including the storage of raw data and assessment results, automatic weighting of data, parameter selection and automated reassessments. This allows the establishment of reproducible up-to-date databases. The proposed software, written in python, is applied to the assessment of a kinetic database for the fcc Co–Cr–Fe–Mn–Ni high entropy alloy using only tracer diffusion data for a sharp separation of thermodynamic and kinetic data. The established database is valid for the whole composition range of the five-component high entropy alloy.